Conversation analytic role-play method (CARM) for early childhood teacher education. Issue 5 (19th October 2020) - Church, Amelia; Bateman, Amanda
ABSTRACT: Here the authors explore everyday teaching strategies that work to implement early childhood curriculum frameworks, using published transcripts of video-recorded data of real-life teacher–child interactions in early childhood centres in Australia and New Zealand. The analysis uses a conversation analysis approach to reveal the sequences of action (talk and gesture) in the co-construction of pedagogical interactions. The authors illustrate how this approach builds on Elizabeth Stokoe's Conversation Analytic Role-play Method (CARM), helping guide early childhood teachers in their interactions with infants, toddlers and young children. They argue that emphasis on real rather than recalled events and close attention to the sequential organisation of talk are central to understanding teaching and learning in early childhood education. The importance of promoting skills and knowledge in the mechanisms of high-quality interactions – that can respond to different contexts, children and concepts for learning – is emphasised, rather than a prescriptive 'best practice' template.